Characterisation of five factor XI mutations - Mitchell, Michael J.; Dai, Letian; Clarke, John B.; Bolton-Maggs, Paula H. B.; Savidge, Geoffrey F.; Alhaq, Anwar (Thrombosis and Haemostasis, 2007)
A large scale factor XI (FXI) mutation screening program identified a number of novel candidate mutations and previously reported mutations and polymorphisms. Five potential missense mutations were selected for further study; these included two novel missense mutations – Met-18Ile (p.Met1Ile) and Met102Thr (p.Met120Thr), two previously reported missense mutations – Tyr133Ser (Tyr151Ser) and Thr575Met (Thr593Met), and one amino acid substitution previously reported as a polymorphism – Arg378Cys (Arg396Cys). The substitutions were recreated by the site-directed mutagenesis of a FXI cDNA and stably expressed in a BHK-570 cell line. Subsequent analysis of both the conditioned media and cell lysates showed that three of the substitutions, Met-18Ile, Met102Thr andTyr133Ser, prevented secretion of the mutated protein from the transfected cell line, resulting in a cross-reactive material negative (CRM-) phenotype. The remaining two mutants, Thr575Met and Arg378Cys, secreted significant levels of FXI into the conditioned media; however, these mutant FXIs were shown to have negligible factor IX activation activity in an APTT based assay. These results confirmed all five of the missense mutations as being causative of factor XI deficiency, despite one having been previously reported as a polymorphism (Arg378Cys) and one (Tyr133Ser) as a mild mutation – FXI:C 38 U/dl in a homozygous patient.
Keywords: Factor XI; site-directed mutagenesis; expression studies